Law Enforcement towards Arrest by Hand Operation in the Prosecutor’s Office of Lampung Province - Median Suwardi (Faculty of Law, Universitas Lampung, 2021)
The purpose of this research is to find out the results of law enforcement activities between the North Lampung District Attorney and the Kepahiang District Attorney and to find out whether the North Lampung District Attorney and the Kepahiang District Prosecutor's Office have fulfilled the principle of legal certainty in the activity of catching the hands of suspected criminal acts committed by non-governmental organizations. This research method uses normative and empirical approaches, namely normative research, which examines laws and theories. The empirical approach is made by looking at the facts and studying the law in the field. The results of the research on arrest activities carried out by the North Lampung District Prosecutor's Office, and the Kepahiang District Prosecutors' Office were carried out based on an order from the respective head of the state prosecutor's office, both the intelligence team and the joint team based on the order of the head of the state prosecutor's office. The difference between the results of law enforcement on the activities of the Attorney General's Office for Handling the arrest of the hands of the North Lampung Police was because the alleged criminal act was a general crime based on the money handed over to the victim, in contrast to the Kepahiang Prosecutor's Office which stated that the criminal act of corruption was due to the villages’ financial (Dana Desa) losses where there are proven state losses. The North Lampung District Prosecutor's Office and the Kepahiang District Prosecutor's Office have legal certainty in the activity of catching hands against non-governmental organizations who are suspected of committing a criminal act. However, the results of these activities are different.